Efficiency in cycling: a review - Ettema, G.; Lorås, H. W. (European Journal of Applied Physiology, 2009)
We focus on the effect of cadence and work rate on energy expenditure and efficiency in cycling, and present arguments to support the contention that gross efficiency can be considered to be the most relevant expression of efficiency. A linear relationship between work rate and energy expenditure appears to be a rather consistent outcome among the various studies considered in this review, irrespective of subject performance level. This relationship is an example of the Fenn effect, described more than 80 years ago for muscle contraction. About 91% of all variance in energy expenditure can be explained by work rate, with only about 10% being explained by cadence. Gross efficiency is strongly dependent on work rate, mainly because of the diminishing effect of the (zero work-rate) base-line energy expenditure with increasing work rate. The finding that elite athletes have a higher gross efficiency than lower-level performers may largely be explained by this phenomenon. However, no firm conclusions can be drawn about the energetically optimal cadence for cycling because of the multiple factors associated with cadence that affect energy expenditure.